2017
DOI: 10.1177/2398212817711083
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the nucleus accumbens core but not shell reduces motivational components of heroin taking and seeking in rats

Abstract: Background: Deep brain stimulation is explored as a new intervention for treatment-resistant substance use dependence. A candidate brain region is the nucleus accumbens, due to its involvement in reward and motivation. This study aimed to explore effects of NAcore and NAshell deep brain stimulation on aspects of heroin taking and seeking in a self-administration model for rats. Methods: NAcore and NAshell deep brain stimulation was applied during 25 or 100 µg/kg/infusion heroin self-administration on an FR4 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Both the NAcc ( Liu et al, 2008 ; Knapp et al, 2009 ; Guo et al, 2013 ; Schippers et al, 2017 ) and shell ( Knapp et al, 2009 ; Henderson et al, 2010 ; Ma et al, 2013 ; Batra et al, 2017 ) have been shown to be promising DBS targets for SUD for substances such as morphine, alcohol, heroin, and methamphetamine. The underlying treatment mechanism has not been fully understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the NAcc ( Liu et al, 2008 ; Knapp et al, 2009 ; Guo et al, 2013 ; Schippers et al, 2017 ) and shell ( Knapp et al, 2009 ; Henderson et al, 2010 ; Ma et al, 2013 ; Batra et al, 2017 ) have been shown to be promising DBS targets for SUD for substances such as morphine, alcohol, heroin, and methamphetamine. The underlying treatment mechanism has not been fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…NAc DBS has shown promising results for the treatment of SUD ( Liu et al, 2008 ; Knapp et al, 2009 ; Henderson et al, 2010 ; Guo et al, 2013 ; Ma et al, 2013 ; Batra et al, 2017 ; Schippers et al, 2017 ; Yuen et al, 2022b ). Here we hypothesized that the therapeutic effects of NAc DBS may be due to its ability to rapidly modulate tonic dopamine concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…One way to address this issue would be to use a progressive ratio schedule of reinforcement. Future studies should also determine the effect of single vs multipe cycles of DBS on models of relapse such as cue-, stress-, and drug-induced relapse [18,21,48,49,78]). High-frequency DBS of the NAcc shell also produced an increase in cocaine-induced locomotor activity that we interpret as a decrease in tolerance to the psychostimulant effects of cocaine and a decrease in irritability-like behavior that we interpret as a decrease in negative emotional states.…”
Section: Limitationsmentioning
confidence: 99%